Polymorphic variants of glutathione reductase – new genetic markers of predisposition to type 2 diabetes mellitus - Iuliia E. Azarova; Elena Yu. Klyosova; Alexey V. Polonikov (Терапевтический архив, 2021)
Aim. To study the associations of three common single nucleotide variants of the gene encoding antioxidant system enzyme, glutathione reductase GSR with a predisposition to type 2 diabetes (T2D).